Contraband Cell Phone Usage Patterns: An Exploratory Examination of Captured Transmission Data. (December 2016) - Grommon, Eric; Carter, Jeremy G.; Scheer, Charles
Contraband cell phones pose significant challenges for correctional administrators and policy makers. Data to examine the nature of the contraband cell phone problem remains elusive, rendering much of the debate about how these issues have arisen and what can be done to resolve challenges informed by anecdotes. Using a data collection of 425, 443 contraband cell phone-attempted transmissions, the present study provides important empirical evidence of contraband cell phone user behavior. Findings indicate that the calling patterns of contraband cell phone users mirror those of the general public. Phones are most likely used to maintain in-state contact with an intimate network of up to six partners, to entertain oneself, to manage personal finances, or a combination of these motivations.